DESCRIPTION OF WORK HAZARDS IN NURSES AT SMC RS TELOGOREJO (STIKES Telogorejo Semarang, 2023)
The hospital environment has the potential for disease transmission, nurses as implementers of nursing care are at risk of contracting infectious diseases in carrying out their duties. In hospitals there are occupational hazards including biological hazards, chemical hazards, ergonomic hazards, physical hazards, and psychosocial hazards). The purpose of this study was to determine the description of work hazards in nurses at SMC Telogorejo Hospital. This research is a descriptive survey by conducting observations and interviews, nonprobability sampling technique Purposive Sampling type with a large sample size of 228 respondents. The results of this study illustrate that the majority of nurses have exposure to physical work hazards (cold climate), biological work hazards (airborne), chemical hazards (use of disinfectant liquid and handscoon), ergonomic work hazards (medical actions), and psychosocial work hazards (workload). From this study it was found that overall nurses at SMC Telogorejo Hospital were exposed to work hazards in the mild category. It is expected that SMC Telogorejo Hospital monitors and evaluates the application of OHSRS to Nurses in carrying out their duties and responsibilities so as to improve the performance, safety and health of Nurses.